1999
DOI: 10.1016/s0736-5748(98)00069-0
|View full text |Cite
|
Sign up to set email alerts
|

Levels of transforming growth factor alpha (TGF‐a)in human cerebrospinal fluid

Abstract: In this study, we investigated cerebrospinal fluid of patients with various neurological symptoms for the presence of transforming growth factor alpha (TGF-alpha). 41 samples of cerebrospinal fluid were collected by lumbar puncture performed routinely due to the clinical suspicion of neurological disease from 22 females (age 15-80 years, median 42 years) and from 19 males (age 18-82 years, median 48 years). A highly sensitive and specific radioimmunoassay was used to determine the concentration of TGF-alpha in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 14 publications
2
6
0
Order By: Relevance
“…BMP7 [24], TGFb1 and 2 [25][26][27][28][29], PDGF-BB [30], NGF [31] FGF-2 [32,33] and TGF-a [34] have all been identified. Only in a few circumstances are their effects on leptomeningeal cells known.…”
Section: Discussionmentioning
confidence: 99%
“…BMP7 [24], TGFb1 and 2 [25][26][27][28][29], PDGF-BB [30], NGF [31] FGF-2 [32,33] and TGF-a [34] have all been identified. Only in a few circumstances are their effects on leptomeningeal cells known.…”
Section: Discussionmentioning
confidence: 99%
“…That is, infusions of TGF-α or EGF into the third ventricle near the SCN suppressed activity and food consumption and cause weight loss [42]. The SCN could communicate with other areas around the third ventricle via the cerebrospinal fluid; the SCN is known to release at least one peptide into cerebrospinal fluid (vasopressin) [40] and TGF-α has been measured in human cerebrospinal fluid [46]. In addition, EGF receptors, localized by immunohistochemistry or by in situ hybridization, have been reported in hypothalamic areas around the third ventricle [25, 26].…”
Section: Discussionmentioning
confidence: 99%
“…Growth factors such as EGF, FGFb, transforming growth factor‐α (TGF‐α), nerve growth factor (NGF) (Craig et al,1996), insulin‐like growth factor 1 (IGF1) (Pérez‐Martin et al,2003), brain‐derived neurotrophic factor (BDNF) (Goldman,1995), and ciliary neurotrophic factor (CNTF) (Kokoeva et al,2005) have been reported to stimulate in vivo or in vitro adult neurogenesis. Most of them have been reported to be present in the CSF (Van Setten et al,1999; Albrecht et al,2006; Bilic et al,2006). The possibility exists that ependymal cells control access of growth factors from the CSF to the subependyma (cf.…”
Section: Discussionmentioning
confidence: 99%